Пространственное моделирование Лубенецкого городища чернолесской культуры - Дараган, М.Н.; Разумов, С.Н. (Археологічні дослідження в Україні, 2010)
Presented is the new data on Lubenetske hill-fort of Chornoliska culture (the Dnipro River Middle region) obtained in tacheometric survey is presented. The development of 3-dimensional digital model of a site and its surrounding allowed the authors to specify the peculiarities of the structure and of functioning of such hill-forts.